Anomalously high heat capacity of core-softened liquids. (2nd January 2019) - Fomin, Yu. D.
ABSTRACT: Heat capacity is among the most important thermodynamic characteristics of a substance. The behaviour of the heat capacity is well understood in gases and crystals, but not in liquids. A common view on the heat capacity of liquids is that it should be close to the solid-like values close to the melting line and it should approach the gas values in the limit of high temperatures. However, some liquids can show anomalously high magnitudes of isochoric heat capacity. In the present paper, I show that core-softened liquids can demonstrate unusually high magnitude of the heat capacity induced by a structural crossover of the liquid.